Transesophageal echocardiography in patients with cryptogenic cerebral ischemia - Dreger Henryk; Walde Torsten; von Hausen Wolfram; Masuhr Florian; Knebel Fabian; Raab Vanessa; Yuerek Mahsun; Baumann Gert; Borges Adrian C (Cardiovascular Ultrasound, 2009)
Abstract Background In about one third of all patients with cerebral ischemia, no definite cause can be identified (cryptogenic stroke). In many patients with initially suspected cryptogenic stroke, however, a cardiogenic etiology can eventually be determined. Hence, the aim of this study was to describe the prevalence of abnormal echocardiographic findings in a large number of these patients. Method Patients with cryptogenic cerebral ischemia (ischemic stroke, IS, and transient ischemic attack, TIA) were included. The initial work-up included a neurological examination, EEG, cCT, cMRT, 12-lead ECG, Holter-ECG, Doppler ultrasound of the extracranial arteries, and transthoracic echocardiography. A multiplane transeophageal echocardiography (TEE, including i.v. contrast medium application [Echovist], Valsalva maneuver) was performed in all patients Results 702 consecutive patients (380 male, 383 IS, 319 TIA, age 18–90 years) were included. In 52.6% of all patients, TEE examination revealed relevant findings. Overall, the most common findings in all patients were: patent foramen ovale (21.7%), previously undiagnosed valvular disease (15.8%), aortic plaques, aortic valve sclerosis, atrial septal aneurysms, regional myocardial dyskinesia, dilated left atrium and atrial septal defects. Older patients (> 55 years, n = 291) and patients with IS had more relevant echocardiographic findings than younger patients or patients with TIA, respectively (p = 0.002, p = 0.003). The prevalence rates of PFO or ASD were higher in younger patients (PFO: 26.8% vs. 18.0%, p = 0.005, ASD: 9.6% vs. 4.9%, p = 0.014). Conclusion A TEE examination in cryptogenic stroke reveals contributing cardiogenic factors in about half of all patients. Younger patients had a higher prevalence of PFO, whereas older patients had more frequently atherosclerotic findings. Therefore, TEE examinations seem indicated in all patients with cryptogenic stroke – irrespective of age – because of specific therapeutic consequences.